Youth criminal intentions under the scope of the theory of planned behavior - Lara-Paredes, Selena Jouly; Alcívar-Junco, Genesis del Carmen; Pérez-Cepeda, Maximiliano (Revista de Ciencias Sociales, 2024)
Using the Theory of Planned Behavior, this research aimed to analyze the effect of attitudes, the social environment and perceived control over the law, to understand criminal intentions of young people in Ecuador, a country that has experienced a significant increase in crime. juvenile delinquency in recent years. 202 students between 14 and 17 years old from five public schools in Ecuador participated in the non-experimental cross-sectional study. The results of the Structural Equations Model show a negative relationship between Attitude and intention (-0.367; p<001), and positive relationships between Subjective Norm and intention (0.333; p<001), and Perceived Control and intention to not commit illegal acts (0.204; p<001). It is concluded that the Theory of Planned Behavior is an adequate framework to understand the effect that individual attitudes, the social environment and the control they perceive over the law have on the intention not to commit illegal acts. The most notable contribution of this research is the inverse relationship between attitude and intention, which raises important questions about the perception of severity that young people have about the law and their intention not to contravene it.